The effect of 8-week core exercises applied to 10-12 age male swimmers on swimming performance - Eskiyecek, C. G.; Gül, M.; Uludag, B.; Gül, G. K. (International Journal of Applied Exercise Physiology, 2020)
The aim of this study was to investigate the effects of core exercise on 50 meter freestyle, backstroke, butterfly and breaststroke style performances of 10-12 year old males swimmers. In this study, from Kocaeli Swimming Club 24 volunteer male swimmers, 12 experimentals and 12 controls group were participated. 3 days a week for 8 weeks; in addition to club swimming trainings, the experimental group received core exercises and the control group received club swimming trainings only. Before and after the training program, height and body weights of all swimmers, and 50 meter freestyle, backstroke, butterfly and breaststroke techniques were obtained in seconds. Wilcoxon test was used for intra-group comparisons and MannWithney-U test was used for first and post-test measurements of swimmers. At the end of the training, a statistically significant difference was found in the experimental group in 50 m swimming first and last test measurements; difference in freestyle; 0.42 sec, backstroke; 0.30 sec, butterfly stroke; 0.47 sec and breaststroke style 0.49 sec (p< .05). A statistically significant difference was found in the control group in 50m swimming first and last test measurements; difference in freestyle; 0.08 sec, backstroke; 0.14 sec, butterfly stroke; 0.18 sec and breaststroke style; 0.13 sec (p< .05). When the significance level between the groups was examined; significant difference was found in favor of experimental group in all measurements (p< .05). As a result of the research, it can be said that core training has a positive effect on swimming performance of male swimmers.